Study of low frequency FOPEN imaging - Na, Yibo (2008)
In this thesis, two relatively novel SAR imaging algorithms, namely the back-projection algorithm and range migration algorithm, are studied. As well, a new approach of range migration algorithm is developed. In their application to FOPEN SAR imaging, performance comparison is made by theoretical analysis, simulation and experimental results. It will be shown that both of these two algorithms are suitable for FOPEN radar imaging where theoretical imaging results can be achieved. The thesis also presents some aspects of image formation in both image (spatial time) domain and phase history (spatial frequency) domain.